Politics Comes from Daily Life Reflections (Armada Riyanto Political Philosophy Perspective) - Juli Antonius Sihotang (Universitas Medan Area, 2021)
This article explores and describes the chaotic world of Indonesian politics, which has often become a theme of public discussion, especially politicians in many events. Problems focused on the world of politics were campaigns, debates, tactics, and arguments from politicians. It makes the world of politics often show the winners and the losers. At the same time, the real world of politics is also a realm to reflect on daily life. In reflecting, he invited a politician to explore the nobility of his dignity and others. Brought him to discover the depths of his life with others while at the same time discovering the truth. This discovery made a politician realize that the world of politics was not only about campaigns, debates, tactics, and arguments. To gain this problem, using the theoretical reference from Armada Riyanto's thinking. The author collected the data through a literature study and analyzed it qualitatively by collecting and studying various books, journal articles, and other sources related to the author's writings. Hence, the differences, similarities, and novelties of the author's pieces could be seen. This study concluded that the depth of life and truth guides a politician not to be naive in following orders, carrying out the law, and which must defeat politicians in tactics and strategies. Politics should be synonymous with honesty, justice, and brotherhood among politicians.